Management Accounting Practices Among Malaysian Local Governments: An Exploratory Study - Isa, Che Ruhana; Saleh, Zakiah; Jusoh, Ruzita (Asian Journal of Accounting Perspectives, 2011)
The main aim of this research is to review the frameworks currently developed and practiced in the public sector, in particular, the Malaysian local governments, and to identify the requirements for a better framework that can secure management control and facilitate accountability to users, the public and interested stakeholders. Specifically, this study investigates the management accounting and control practices, and the micro-accounting systems used by the local governments. It also examines the extent of the reforms or changes in these systems and the extent of micro-accounting implementation in these organisations. Among the management accounting practices, the results reveal that local government organizations are heavily involved with budgeting and performance measurement tools and show reasonable interest in accountability issues.